2015
DOI: 10.15436/2376-0494.15.015
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Type 2 Diabetes Among Us and Foreign Born Non-Hispanic Asians: Evidence From Nhanes 

Abstract: Aims/Introduction: The purpose of this study was to compare risks for metabolic dysfunction and type 2diabetes among Non-Hispanic Asian and Non-Hispanic white adults using new nationally representative data in the U.S. We compared the metabolic profiles of U.S.-born vs. foreign -born Non-Hispanic Asian adults. Materials and Methods: This study used NHANES 2011-2012 adult data for Non-Hispanic Asians (n=827) and Non-Hispanic Whites (n=2,108). Standardized risk threshold cutoffs for blood pressure, lipids, and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
1
1
Order By: Relevance
“…Analysis of NHANES 2011-2012 found that that foreign born Asian Americans were at elevated risk for high total cholesterol and LDL levels [24]. These results contrast with our findings of higher non-LDL (b=26.55, p<0.001), higher LDL levels (b=19.82, p=0.01), and lower HDL levels (b=-4.00, p=0.01) amongst US born Asian American adolescents.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Analysis of NHANES 2011-2012 found that that foreign born Asian Americans were at elevated risk for high total cholesterol and LDL levels [24]. These results contrast with our findings of higher non-LDL (b=26.55, p<0.001), higher LDL levels (b=19.82, p=0.01), and lower HDL levels (b=-4.00, p=0.01) amongst US born Asian American adolescents.…”
Section: Discussioncontrasting
confidence: 99%
“…Echeverria et al studied adults using NHANES 2011-2014 and found that Asian Americans had an increased prevalence for CVD risk factors with longer durations in the US [5]. Analysis of NHANES 2011-2012 found that that foreign born Asian Americans were at elevated risk for high total cholesterol and LDL levels [24]. These results contrast with our findings of higher non-LDL (b=26.55, p<0.001), higher LDL levels (b=19.82, p=0.01), and lower HDL levels (b=-4.00, p=0.01) amongst US born Asian American adolescents.…”
Section: Discussionmentioning
confidence: 99%